Comparison of Accuracy of IOL Master and a Scan Acoustic Biometry in Silicon Oil Filled Eyes - Faisal Anwar, Asad Aslam Khan, Tehseen Mahmood Majhu, Rana Mohammad Mohsin Javaid, M. Hasan Bokhari, M. Tahir Ghaffar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Objective of our study was to determine accuracy of IOL Master and A scan acoustic biometry in silicon filled eyes in terms mean difference of axial length pre-operatively and mean post-operative refractive error Study design: Comparative cross sectional study Study settings and duration: Study was conducted at department of Ophthalmology (Eye Unit III) Mayo hospital Lahore (KEMU) from November 2019 to April 2020. Material and methods: WHO calculator was used for calculation of patient sample (N=34). Patients were randomly divide in two groups Group I underwent preoperative axial length (AXL) measurement by using IOL Master and by acoustic a-scan ultrasound in Siliconized mode. Results: Total 34 patients were included in study. There were 18(52.9%) male and 16(47.1%) female. Mean age of patients was 44.2±6.4 years. Patients undergone biometry with Master IOL showed better visual acuity (Log Mar) (0.25±0.7, 0.63±0.09, p=0.000), less post-operative refractive error (0.22±0.02, 0.72±0.17, p=0.000) as compared to those in which A scan acoustic biometry was done. A significant difference in post-operative axial length was reported (p=0.04) Conclusion: IOL master is more accurate and reliable method of IOL power calculation resulting in better visual outcomes and less post-operative refractive error as compared to A scan acoustic biometry in silicon filled eyes.